The Position of Sunanī (Divine Law) Thinking in the Movement of Contemporary Thought Reformation - Kohooss, Raheed (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2023)
The aim of this study is to highlight the position of Sunanī thought (Divine Law that governs human beings and nature) in the movement of contemporary thought reformation in the East and the West through examining representative projects of contemporary thinkers and detecting the Sunanī consciousness that guides this movement. The study reveals the presence of Sunanī consciousness in the thought of many contemporary thinkers, evident in their adherence to the guiding Sunanī approach of reading history, perceiving and critiquing the present, and foreseeing the future. The study presents three contemporary schools: the school of contemporary exegetes, the school of thinkers, and that of the Islamization of knowledge. The study reaches the conclusion that contemporary Islamic thought is still affiliated with Sunanī thought as one of the most important crucial and decisive issues for the nation, the study of which is key to: finding solutions to numerous contemporary social and civilizational problems; answering many of the vital present-day questions relating to life, existence, and mankind; and providing a profound comprehension of theological matters such as fate, destiny, human acts, predestination, and free will, among others.